Ritual Roots of Memory (About Things) - Karski, Kamil (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2015)
The aim of this paper is a presentation of possible interpretations of the ritual of salutatio, as well as function and cultural connotations of ancestral funerary portraits (imagines) in ancient Rome. For this purpose, a number of research theories related to memory studies, hermeneutical analyses and performativity of things are discussed. In light of these theories it is possible to attempt an interpretation of salutatio and imagines as sources for constructing identity and memory of the Roman community.
Rytualne źródła pamięci (o rzeczy)
Keywords: memory studies; hermeneutics; biography of things; ritual; salutatio